An Analysis of Teachers’ Questioning Strategies during the Classroom Interaction (A Descriptive Qualitative Research on SMK Negeri 1 Paloh) - Nursikin; Rezeki, Yanti Sri; Wardah (Kirana Publisher (KNPub), 2024)
A good teaching-learning process involves students and teachers as a single main source in the classroom. Student participation is essential in the teaching-learning process because it allows for good interaction between teachers and students. Teachers' questioning strategies can encourage students to participate more actively in the language-learning process. Teachers must use questioning strategies because they are one of the factors that contribute to an effective teaching and learning process. The purpose of this study was to learn about the types of English teachers' questioning strategies and why they used them in their classroom interactions at SMK Negeri 1 Paloh. In this study, the writer used a descriptive qualitative method. To collect data, the writer conducted classroom observations and recorded audio interviews. The data was collected from two English teachers at SMK Negeri 1 Paloh who teach in grades X and XI to determine the types of questioning strategies used and why they were used during classroom interactions. Based on the observations, the study findings indicate that the teachers asked procedural, convergent, and divergent questions. During the classroom interaction in which they were asked the question, the English teachers actively used question strategies to assess the student's understanding of the previous material, to attract the students' attention, to support the students' contributions in class, and to motivate the students to learn. As a result, the English teacher used their questioning strategies in their teaching-learning process, and the students were more active and confident in their ability to understand and answer questions.